EXAMINING THE USE OF ICT STORAGE AND DISSEMINATION OF LIBRARY MATERIALS IN ACADEMIC LIBRARIES IN GHANA - Plockey, F. D.; Pwadura, J. (UDS International Journal of Development, 2018)
Information and Communication Technology (ICT) has transformed library and information services from the concept of storehouses of books to the concept of libraries without walls. Academic libraries exist to support the academic community. Their main functions include selection, collection, production, documentation, organization, preservation, organization, storage, dissemination and exchange of library materials. This study seeks to examine in detail, the role of ICT in the storage and dissemination procedures of Library materials in academic libraries in Ghana. The instruments for data collection were interviews coupled with observation and the researchers’ experience as Assistant Librarians in an academic library. The responses demonstrate that, academic library materials come in different formats and are stored differently depending on the nature of the material. The libraries under study use multi-strand approach to disseminate information to ensure wide coverage. Keywords: Storage of Library Materials, Dissemination, Print media, Non- Print Media, Academic Libraries